1996
DOI: 10.1302/0301-620x.78b4.0780584
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Necrosis After Tibial Reaming for Intramedullary Nail Fixation

Abstract: We present three young men who sustained closed diaphyseal fracture of the tibia and later developed severe osteocutaneous necrosis induced by heat during intramedullary reaming. They all had a narrow medullary cavity and in all a tourniquet had been used. Each developed a pretibial cutaneous blister soon after operation. In the following month severe osteomyelitis ensued, requiring segmental resection and osteocutaneous reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 21 publications
0
61
0
5
Order By: Relevance
“…There are many studies that document the severe disruption of endosteal circulation with reaming and subsequent bone necrosis [4,16,19,25]. Klein et al demonstrated a severe vascular insult with aggressive reaming in dog tibiae [17]; Melcher showed an increased rate of infection with reaming in rabbit tibia fractures [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that document the severe disruption of endosteal circulation with reaming and subsequent bone necrosis [4,16,19,25]. Klein et al demonstrated a severe vascular insult with aggressive reaming in dog tibiae [17]; Melcher showed an increased rate of infection with reaming in rabbit tibia fractures [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious consequences of local hyperthermia induced by intramedullary reaming as a complication of intramedullary fixation of tibial fractures are occasionally noted in the literature [11,13,15,16]. Friction forces involved in reaming of the intramedullary canal generate a rise in temperature of the surrounding tissues that, under controlled conditions, is reported in vivo between 0.5°C and 16°C for a maximum of 15 seconds [7].…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures as high as 175-225°C after two minutes of reaming have been estimated with subsequent development of irreversible thermal damage to bone and surrounding tissues [1]. We are aware of six reported patients with osteocutaneous thermal necrosis, all involving the tibia [11,13,15]. A seventh case of segmental bone necrosis without associated soft tissue necrosis has been reported after intramedullary reaming of the humerus [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The recent use of locked intramedullary nail has shown promising results. 10 It has also given satisfactory result in proximal third tibial shaft fracture and segmental tibial shaft fracture. 11 Reamed interlocking nails also have comparable results to those of unreamed nailing in open fractures.…”
mentioning
confidence: 96%